Moderation: work culture to improve employee performance with a non-physical work environment - Slamet Riyanto; Liza Mumtazah Damarwulan; Didit Haryadi (Jurnal Mantik, 2022)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become the locomotor in making a real contribution to the organization's success on an ongoing basis. Of course, only employees with optimal performance achieve this success. However, to maximize employee performance, there must be a strategy to increase it. This study aims to find out how this strategy improves employee performance. The PLS-SEM approach is used in this study. The results of this study indicate that the non-physical work environment and culture can affect employee performance. Work culture can strengthen the effect of the non-physical work environment on employee performance